Gas hydrates, flares seeps offshore Romania, a review (Geo-Eco-Marina, 2019)
The civilisation is in the continuous search for energy resources, either already in use or new ones, for future needs. The gas hydrates are one of the unconventional resources that have been identified, evaluated and in the future will be probably exploited. The semi-enclosed Black Sea Basin has an excellent potential for free gas and gas hydrate accumulation, on account of its anoxic water regime which favours the preservation of organic matter in the sediments (the chemocline lies at 110–140 m depth). Regions outside the stability field of gas hydrates, namely, the shelf and upper slope, show a high gas content in the sediments.The Black Sea Basin has been the focus for numerous research projects, which led to the identification of the BSR that might be associated with the gas hydrate zones. Beside the gas hydrates, numerous gas occurrences have been recognized on the seafloor of the Black Sea in different sectors and at different depths, including shelf and slope of Romanian Black Sea area, and a significant amount of data have been published. The current synthesis aims to make a review of the results published in the last 15 years describing geological structure and evolution of the Black Sea Basin, as well as bottom sediments, gas hydrates, flare and escape structures Offshore Romania.
Keywords: Black Sea; unconventional resources; Danube Canyon; landslides; heat flow; deep water